2007
DOI: 10.1021/bi700666m
|View full text |Cite
|
Sign up to set email alerts
|

A Monovalent Mutant of Cyanovirin-N Provides Insight into the Role of Multiple Interactions with gp120 for Antiviral Activity,

Abstract: Cyanovirin-N (CV-N) is a 101 amino acid cyanobacterial lectin with potent antiviral activity against HIV, mediated by high-affinity binding to branched N-linked oligomannosides on the viral surface envelope protein gp120. The protein contains two carbohydrate-binding domains, A and B, each of which binds short oligomannosides independently in vitro. The interaction to gp120 could involve either a single domain or both domains simultaneously; it is not clear which mode would elicit the antiviral activity. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
123
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(133 citation statements)
references
References 41 publications
(82 reference statements)
10
123
0
Order By: Relevance
“…This relation, however, cannot become crystallographic by any alternative unit cell/symmetry definition. The current structure of Cyt-CVNH is similar to previously determined crystal structures of monomeric, nondomain-swapped CV-N variants (22,23), in contrast to the domain-swapped wild type CV-N structures (13,24,25). We ascertained that the x-ray data were incompatible with a domain-swapped dimer structure by omitting the hinge-loop region (Trp 49 -Asn 53 ) in the model employed for molecular replacement.…”
Section: Resultssupporting
confidence: 68%
“…This relation, however, cannot become crystallographic by any alternative unit cell/symmetry definition. The current structure of Cyt-CVNH is similar to previously determined crystal structures of monomeric, nondomain-swapped CV-N variants (22,23), in contrast to the domain-swapped wild type CV-N structures (13,24,25). We ascertained that the x-ray data were incompatible with a domain-swapped dimer structure by omitting the hinge-loop region (Trp 49 -Asn 53 ) in the model employed for molecular replacement.…”
Section: Resultssupporting
confidence: 68%
“…Perhaps Abs with these antigen binding sites readily recognize synthetic high-mannose but not natural high-mannose structures because the linker-dependent presentations described above are also adopted on the printed covalent glycan array. In addition, increased positional fluctuations may disrupt the hydrogen bonding network between the antennae of branched synthetic oligomannosides (e.g., Man 8 and Man 9 ), also facilitating Ab binding (26).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown, however, that both sites are necessary for viral neutralization and that destruction of either site renders the CV-N variant inactive (16,17). However, a recent study showed that in the context of a CV-N dimer that was covalently crosslinked using disulfide bonds, two out of the four possible binding sites are sufficient to maintain neutralization activity, indicating that it is the number and not the identity of sites that is important for neutralization (18,19).…”
mentioning
confidence: 99%